CONTENT DEVELOPMENT OF HYDRONYMIC WORDS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article talks about hydronyms, a group of words related to the names of water bodies and rivers of toponymy. Historical formation, content and structural development of hydronyms are analyzed. It is analyzed with examples, dividing into groups.